2018
DOI: 10.1007/s10803-018-3521-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Co-occurring Medical and Behavioral Conditions/Symptoms Among 4- and 8-Year-Old Children with Autism Spectrum Disorder in Selected Areas of the United States in 2010

Abstract: We compared the prevalence of various medical and behavioral co-occurring conditions/symptoms between 4- and 8-year-olds with autism spectrum disorder (ASD) from five sites in the Autism and Developmental Disabilities Monitoring Network during the 2010 survey year, accounting for sociodemographic differences. Over 95% of children had at least one co-occurring condition/symptom. Overall, the prevalence was higher in 8- than 4-year-olds for 67% of co-occurring conditions/symptoms examined. Further, our data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
157
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 48 publications
8
157
0
2
Order By: Relevance
“…Paquet et al [] reported motor difficulties in 41% of children with ASD ( N = 34, 4–11 years, 44% with ID), Dewey et al [] reported 59% ( N = 49, 5–18 years, 10% with ID), Liu and Breslin [] reported 77% ( N = 30, 3–16 years, no ID), and Green et al [] reported 79% ( N = 101, 10–14 years, 35% with ID). While studies evaluating prevalence based on the review of clinical records have reported a lower prevalence than we identified in our standardized parent‐report measure, with Soke, Maenner, Christensen, Kurzius‐Spencer, and Schieve [] reporting motor difficulties in 24% of children aged 4 years ( N = 607, 20% with ID) and 29% aged 8 years ( N = 749, 15.6% with ID). The inconsistency between studies likely reflects varying sample sizes and age ranges, core and/or co‐occurring symptomology of samples, and method of evaluation.…”
Section: Discussionmentioning
confidence: 85%
“…Paquet et al [] reported motor difficulties in 41% of children with ASD ( N = 34, 4–11 years, 44% with ID), Dewey et al [] reported 59% ( N = 49, 5–18 years, 10% with ID), Liu and Breslin [] reported 77% ( N = 30, 3–16 years, no ID), and Green et al [] reported 79% ( N = 101, 10–14 years, 35% with ID). While studies evaluating prevalence based on the review of clinical records have reported a lower prevalence than we identified in our standardized parent‐report measure, with Soke, Maenner, Christensen, Kurzius‐Spencer, and Schieve [] reporting motor difficulties in 24% of children aged 4 years ( N = 607, 20% with ID) and 29% aged 8 years ( N = 749, 15.6% with ID). The inconsistency between studies likely reflects varying sample sizes and age ranges, core and/or co‐occurring symptomology of samples, and method of evaluation.…”
Section: Discussionmentioning
confidence: 85%
“…Medical and psychiatric co‐occurring conditions represent a sizable burden on participants and their families [Croen et al, ; Jokiranta‐Olkoniemi et al, ; Soke, Maenner, Christensen, Kurzius‐Spencer, & Schieve, ]. Information reported was as follows: 74% with at least one co‐occurring neurodevelopmental, psychiatric, or neurological condition and 93% with at least one general medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that ASD is defined by behavior, it is now recognized as being associated with a large number of co‐occurring medical conditions (COCs) beyond the core behavioral symptoms [Tye, Runicles, Whitehouse, & Alvares, ]. A recent study from the Autism and Developmental Disabilities Monitoring Network found over 95% of children with ASD to be affected by at least one COC [Soke, Maenner, Christensen, Kurzius‐Spencer, & Schieve, ]. Although the economic costs of caring for a child with ASD are already elevated compared to those for a typically developing child, these costs are further increased by the presence of COCs [Buescher, Cidav, Knapp, & Mandell, ; Horlin, Falkmer, Parsons, Albrecht, & Falkmer, ; Lavelle et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the need for timely diagnosis of COCs, which is made difficult by substantial variation in their occurrence with age. One study reported a higher prevalence of most evaluated COCs in 8‐year‐old children with ASD compared to 4‐year‐olds [Soke et al, ]. Changes in prevalence of GI symptoms and sleep problems over 2 years of follow‐up have also been observed in individuals with ASD [Mannion & Leader, ], although it is unclear whether this difference in prevalence simply results from difficulty diagnosing COCs early in life.…”
Section: Introductionmentioning
confidence: 99%